Line Generalization Evaluation on Contour Map Generated From SRTM and ASTER GDEM - Totok Wahyu Wibowo (Journal of Applied Geospatial Information, 2018)
A contour map is one of many layers that composed Informasi Geospasial Dasar (IGD), which according to Act. No 4 2011 serves as a reference for any thematic map. The provision of contour map at a different level of scale is needed since mapping activities will always refer to map scale based on the mapping area. This research aims to analyze automated contour generation quality to produce 1:50.000 contour map, by means of using open access Digital Elevation Model (DEM) data, such as Shuttle Radar Topographic Mission (SRTM) and Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Digital Elevation Model (GDEM). The automated contour generation was done by using contour interpolation in Quantum GIS software. Furthermore, simplification and smoothing algorithm was applied to both data, in order to improve their visual appearance. In this case, there are four algorithms used in the study, namely Douglas-Peucker, Visvalingam, Chaikin, and McMaster. Quality assessment, both qualitative and quantitative assessment, was done to each derived contour map to ensure the applicability of the procedure. The result shows that contour map generated from SRTM has a better quality than contour map generated from ASTER GDEM. Nevertheless, both data has a similar pattern on each topographical classes, which tends to produce bad quality contour line in the flat area. The more mountainous the area, the better the contour line. Meanwhile, of all generalization algorithm applied in this study, Chaikin’s algorithm is the best algorithm in terms of smoothing the contour line and improving visual quality, but still doesn’t significantly improved the metric accuracy. The contour line can be either directly added to the Digital Cartographic Model of Topographic Map (Rupabumi Map), or used as compliance data in a thematic map.